The Management of Drinking Water and Long-term Perspective: Tunisia Case - Bouchrika, Ali; Bardi, Wajdi (International Journal of Economics and Financial Issues, 2016)
This article analyzes the current situation of the management of drinking water in Tunisia, focusing on the constraints that the said management is subject. The empirical results show the absence of a long-term equilibrium between production capacity and consumption structure. In addition, the pricing policy is not an incentive tool to lower consumption. In fact, for domestic sector, water appears as a necessary good, while for both industry and tourism sectors declining consumption due respect to the fact that these two sectors have adopted other sources of supply substituting water of the National Water Distribution Utility. In addition to these three sectors, the hypothesis of cointegration (long-term equilibrium relationship) between the level of consumption, the price and the number of subscribers is rejected in most cases. To solve these problems, we propose a new pricing structure based primarily on the size of households to reduce waste. Keywords: water management, pricing policy, cointegration, simultaneous equations. JEL Classifications: C22, Q21, Q25